Friday, January 27, 2012

`1, 5, 9, 13...` Use mathematical induction to find a formula for the sum of the first n terms of the sequence.

`1,5,9,13,......`


Now let's denote the first term` ` of the above sequence by `a_1` and k'th term by `a_k` and let's write down the first few sums of the sequence.


`S_1=1`


`S_2=1+5=6=(2(1+5))/2=(2(a_1+a_2))/2`


`S_3=1+5+9=15=(3(1+9))/2=(3(a_1+a_3))/2`


`S_4=1+5+9+13=28=(4(1+13))/2=(4(a_1+a_4))/2`


From the above sequence it appears that the formula for the sum of the k terms is,


`S_k=(k(1+a_k))/2`


Now the difference between the consecutive terms of the series is 4, so we can write down ,


`a_k=1+(k-1)4=1+4k-4=4k-3`


`a_(k+1)=4(k+1)-3=4k+4-3=4k+1`


`S_k=(k(1+4k-3))/2=(k(4k-2))/2`


`S_k=k(2k-1)`


Now we can verify that it is valid for n=1,


Plug in k=1 to verify,


`S_1=1(2*1-1)=1`


Let's assume that the formula is valid for n=k and now we have to show that it is valid for n=k+1


`S_(k+1)=1+5+9+13........+a_k+a_(k+1)`


`S_(k+1)=S_k+a_(k+1)`


`S_(k+1)=k(2k-1)+4k+1`


`S_(k+1)=2k^2-k+4k+1`


`S_(k+1)=2k^2+3k+1`


`S_(k+1)=2k^2+2k+k+1`


`S_(k+1)=2k(k+1)+1(k+1)`


`S_(k+1)=(k+1)(2k+1)`


`S_(k+1)=(k+1)[2(k+1)-1]`


So the formula is valid for n=k+1 also, 


So the formula can be written as ,


`S_n=n(2n-1)`

No comments:

Post a Comment

How does the choice of details set the tone of the sermon?

Edwards is remembered for his choice of details, particularly in this classic sermon. His goal was not to tell people about his beliefs; he ...